The end of MINUSMA in Mali and the future of stabilization peace operations - Carvalho, Letícia (2024)
In this article, we will discuss the process that led to the ending of MINUSMA, the stabilisation peace operation carried out by the UN in Mali between 2013 and 2023, and we will make a brief conjunctural analysis of this moment of withdrawal, considering its consequences both in terms of the political situation in the country and the abuses and human rights violations suffered by the civilian population, bearing in mind that stability and the protection of civilians were among the mission’s main objectives when it was deployed. Methodologically, the work is based on a qualitative analysis of data on MINUSMA’s performance in Mali throughout its mandate, and on the political situation in the country today, with a focus on the occurrence of violent episodes and fatalities, possible advances related to the political process of conflict resolution and the protection of civilians. The main sources used were documents and reports from the UN itself, non-governmental organizations and research institutes on Mali in general and on MINUSMA’s activities and withdrawal process specifically.